2012
DOI: 10.1007/s10096-011-1513-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-invasive fibrosis markers and classical liver biopsy in chronic hepatitis C

Abstract: The aim of this study was to compare the results of nine non-invasive serum biomarkers with liver biopsies to predict liver fibrosis stage. HCV-RNA-positive, HCV genotype 1, treatment-naive patients with chronic HCV infections were included from 14 centers (n=77). The platelet count, AST/ALT ratio (AAR), cirrhosis discriminate score (CDS), FIB4, AST/platelet ratio index (APRI), age-platelet (AP) index, Göteborg University cirrhosis index (GUCI), FibroTest, and ActiTest were calculated and compared to histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
3
14
1
9
Order By: Relevance
“…The mean AUROC values were found to be 0.71−0.83; sensitivity, specificity, PPV, and NPV were found to be 62%−74%, 60%−77%, 37%−83%, and 76%−94.7%, respectively, according to various cut-offs in the studies performed with FIB-4 (10,22,(24)(25)(26)28,30,31). In our study, according to the Ishak and Knodell classifications, the mean AUROC values in the diagnosis of significant/severe fibrosis were −0.72 and -0.67, respectively, and sensitivity, specificity, PPV, and NPV were found to be 67%−70%, 61%−68%, 17%−30%, and 88-96%, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The mean AUROC values were found to be 0.71−0.83; sensitivity, specificity, PPV, and NPV were found to be 62%−74%, 60%−77%, 37%−83%, and 76%−94.7%, respectively, according to various cut-offs in the studies performed with FIB-4 (10,22,(24)(25)(26)28,30,31). In our study, according to the Ishak and Knodell classifications, the mean AUROC values in the diagnosis of significant/severe fibrosis were −0.72 and -0.67, respectively, and sensitivity, specificity, PPV, and NPV were found to be 67%−70%, 61%−68%, 17%−30%, and 88-96%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…NPV and PPV have been found to be 86%-88% for the detection of significant fibrosis and cirrhosis (9). However, in later studies, a wide range of sensitivity, specificity, PPV, NPV, and AUROCs values were found: 71%-97%, 13%-74%, 34%-84%, 43%-92%, and 0.6%-0.86, respectively (9,10,(22)(23)(24)(25)(26)(27)(28)(29). The occurrence of different results may be associated with the number of patients with significant fibrosis and AST.…”
Section: Discussionmentioning
confidence: 98%
“…A májbiopszia invazív beavatkozás. A betegek 30%-a érez fájdalmat a mintavétel után [4]. A szövődmények (vérzés, epecsorgás, légmell) előfordulása 0,3-0,6%, a beavatkozás halá-lozása 0,009-0,12 [4].…”
Section: öSszefoglaló Közleményunclassified
“…20-80%-a érez fájdalmat a mintavétel után [1]. A szö-vődmények (vérzés, epecsorgás, légmell) előfordulása 0,3-0,6%, a beavatkozás halálozása 0,009-0,12 [1,2].…”
unclassified
“…A szö-vődmények (vérzés, epecsorgás, légmell) előfordulása 0,3-0,6%, a beavatkozás halálozása 0,009-0,12 [1,2]. A májbiopszia ellenjavallt megnyúlt protrombinidő (INR>1,6), thrombocytopenia, ascites, bonyolult testalkati viszonyok, haemangioma vagy echinococcus-fertő-zés gyanúja, illetve az együttműködés hiánya esetén.…”
unclassified